NECESSITY OF DEVELOPING HUMANISM IN STUDENTS (International journal of artificial intelligence, 2025)
This article examines the necessity of developing humanism among students from scientific and pedagogical perspectives. It highlights the importance of fostering social-emotional competencies, the role of humanism in modern education, and effective methods based on international practice. A survey conducted among university students revealed that the levels of empathy, tolerance, and cooperation remain moderate. Based on the findings, recommendations are proposed to strengthen humanistic education within Uzbekistan’s higher education system.